US Latino adolescents' use of mass media and mediated communication in romantic relationships*. Issue 4 (1st October 2016) - Len-Ríos, María E.; Streit, Cara; Killoren, Sarah; Deutsch, Arielle; Cooper, M. Lynne; Carlo, Gustavo
Abstract: The present study uses uncertainty reduction theory to analyze how Latino adolescents perceive that mass media influence their conceptions of romantic relationships. In addition, we explore how these adolescents use social media in their romantic relationships. Data are from five focus groups with 44 Latino adolescents ( M = 16.39 years old; 59% female) in the US Midwest. Findings indicate that Latino adolescents believe media portray unrealistic ideals of romantic relationships, yet these teens also see the portrayals as ideals to which they should aspire. When it comes to social media, the youth perceived one-to-one mediated communication (e.g. Skype) as beneficial to their romantic relationships, but evaluated one-to-many mediated communication (e.g. Facebook, Instagram) as largely negative. Our findings identify three sources of evidence in the latter context that create relational uncertainty: (1) visual, (2) partner communication, and (3) third-party communication.